Education visit to the Monetary Authority of Singapore: a global insight into financial regulation - Mejri, Norazimah (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The visit to MAS Gallery further enriched their experience, showcasing the evolution of Singapore's monetary system, the history of its economic policies, and its vision for a future- ready financial sector. A highlight of the trip was a simulation activity that challenged students to analyse economic data and make policy recommendations, simulating the real-world pressures of central banking and regulatory decision-making. This not only strengthened their practical understanding of monetary tools but also fostered critical thinking, teamwork, and effective communication.